2017
DOI: 10.1139/bcb-2016-0066
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin and prematurity: a promising milk protein?

Abstract: Lactoferrin (Lf) is the major whey protein in milk with multiple beneficial health effects, including direct anti-microbial activities, anti-inflammatory effects and iron transporter. Iron homeostasis in the foetus, the neonate and preterm infant is crucial for adequate growth and development. Lf oral supplementation in human preterm infants has been shown to reduce the incidence of sepsis and necrotizing enterocolitis. In preclinical models of antenatal stress and perinatal brain injury bovine Lf protected th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 111 publications
0
27
0
2
Order By: Relevance
“…Lactoferrin (Lf) is the major whey protein in milk, with multiple beneficial health effects including direct antimicrobial activities, anti‐oxidant, anti‐inflammatory effects, and in iron homeostasis has recently been evaluated in different animal models of developmental brain injury (Ochoa and Sizonenko, 2017). Whereas Lf has shown supportive effects on early postnatal brain development and function trough increased BDNF expression (Chen et al, 2015; Shumake et al, 2014), it has also showed protective effects in dexamethasone‐induced IUGR brain alterations when given as supplement to dam during gestation and lactation.…”
Section: Dietary Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lactoferrin (Lf) is the major whey protein in milk, with multiple beneficial health effects including direct antimicrobial activities, anti‐oxidant, anti‐inflammatory effects, and in iron homeostasis has recently been evaluated in different animal models of developmental brain injury (Ochoa and Sizonenko, 2017). Whereas Lf has shown supportive effects on early postnatal brain development and function trough increased BDNF expression (Chen et al, 2015; Shumake et al, 2014), it has also showed protective effects in dexamethasone‐induced IUGR brain alterations when given as supplement to dam during gestation and lactation.…”
Section: Dietary Interventionsmentioning
confidence: 99%
“…Similar results of neuroprotective effects where shown in a model of LPS induced inflammation at P3 in rat pups receiving LF through lactation from the day of birth (Ginet et al, 2016). In addition, its clinical effect on reducing preterm neonatal infection and necrotising enterocolitis makes it a good candidate for neonatal use and should be further tested in prenatal conditions for neuroprotection, infection protection and also preterm delivery prevention (Ochoa and Sizonenko, 2017).…”
Section: Dietary Interventionsmentioning
confidence: 99%
“…Для детей первого года жизни особенно важны антибактериальные, противовирусные, противо-грибковые и противопаразитарные свойства лактофер-рина [14]. Кроме того, подтверждены его каталитическая активность, противоаллергические, иммуномодулирую-щие и радиопротекторные свойства [15].…”
Section: лактоферрин -иммуногенный белок молокаunclassified
“…Особую роль назначение лактоферри-на играет в профилактике возникновения инфекционной патологии: у недоношенных, детей со сниженным имму-В практику педиатра нитетом, нарушениями нутритивного статуса, после пере-несенных хирургических вмешательств и др. [14,43,44].…”
Section: лактоферрин -иммуногенный белок молокаunclassified
“…Villavicencio et al (2017), have extensively reviewed the factors that affect lactoferrin concentration in human milk and colostrum. In another report, Ochoa and Sizonenko (2017) review the functions of Lf in neonates and preterm infants, including roles in the barrier function of the intestinal mucosa, modulation of the intestinal microbiome, and effects of Lf on the developing brain. Notably, Lf, like melanotransferrin and transferrin, readily crosses the blood-brain barrier (Abbott et al 2010).…”
Section: Introductionmentioning
confidence: 99%